Congenital anterior abdominal defects. Issue 12 (December 2016) - Kelay, Arun; Durkin, Natalie; Davenport, Mark
Abstract: Anterior abdominal wall defects are a common cause of morbidity and even mortality. These include gastroschisis, usually an isolated defect, and exomphalos, a more fundamental cause of abdominal wall failure often seen in association with chromosomal and other systemic anomalies. The worldwide incidence of gastroschisis has risen inexorably over the past 30 years, whereas the incidence of exomphalos, at least at the time of birth, has been relatively static. This article provides an overview of the key aspects of antenatal, perinatal and postnatal management, highlighting areas of controversy where further study is required.